The Field Notes - The Heavens 2019 - Pietarinen, Heidi; Grant, Melissa; de Peyer, Oliver; Bovermann, Till; Yoncha, Anne; Sandgren, Noora (2019)
High Altitude Bio-prospecting – Extremophiles:Psychrophiles:Cryobiosis The copiously branching tree of life reveals that life can exist almost anywhere on Earth. Eighty percent of the biosphere, including the deep oceans, the cryosphere at the planet’s poles and the high atmosphere where the focus of HAB locates, is permanently cold. Yet we know relatively little about cold defying organisms: where do they live? How do they survive? Can we find them? Research suggests that there are microbes above us seeding snowflakes and rain clouds and as such instrumental for life on the ground, forming a shell which is part is seemingly part of every ecosystem on this planet. They may be few and far between – will lengthy flights be needed to find them? Can contact be made? Can we sample the high atmosphere and discover unique extremophiles and psycrophiles that live and thrive? With a transdisciplinary group HAB will seek strategies to investigate the high atmosphere above the subarctic Kilpisjärvi and explore how to think about the relationship between the ecologies of the ground and the sky from the perspective of art and the sciences.